Telework and work-family conflict during COVID-19 lockdown in Portugal: The influence of job-related factors - Cláudia Andrade; Eva Petiz Lous\~a (Administrative Sciences, 2021)
Even though research has been showing that telework, under regular circumstances, could benefit the integration of work and family life, mandatory telework during the COVID-19 lockdown brought additional challenges, with potential to create conflicts between work and family spheres. Using regression analysis, this study examined the contribution of demographic and job-related variables to the prediction of work-family conflict among a sample of 213 workers who were involved in mandatory telework during the first lockdown due to the COVID-19 pandemic. The results revealed that role overload, after-hours work-related technology use, and low job autonomy accounted for the prediction of work-family conflict. Support from the supervisors and coworkers did not have an impact in easing the perception of work-family conflict but presented a moderation effect between after-hours work-related technology use and work-family conflict. Implications of the study for management practices related to telework, limitations of the study, and directions for future research are discussed.
Keywords: 350; COVID-19; telework; work-family conflict